A arbitragem como meio de solução de litígios em parcerias empresariais para a promoção de empreendimentos imobiliários - Moreira, Yann Cabral (2023)
Arbitration is a legal institute that has long offered people an alternative to the common jurisdiction exercised by the Judiciary, in order to resolve disputes on the most varied topics, as long as they deal with available rights and respect the legal order. An important figure in arbitration is the arbitrator, responsible for appreciating the demands and delivering an adequate decision. This arbitrator or arbitration entity will be defined by the parties and a good choice, by the most varied methods and within the autonomy of the will, will be essential for a quick, technical and adequate judgment. Thus, through this work, we seek to present to the reader the complexity of real estate partnerships for the development of new urban projects, demonstrating that the adoption of arbitration as a means of resolving possible conflicts can be more advantageous and more appropriate. The advantages emerge from several factors, such as the deadline for obtaining the sentence, the reduction of the possibility of appeals, appointment of arbitrators endowed with technical expertise in the area of interest, among others. After the considerations made here, we propose an analysis of the national history of arbitration, we approach the legal requirements on which it can deal and be instituted, we expose how real estate deals for new ventures are constituted and the advantages in the respective choice. Finally, we propose the adoption of dispute board as a skillful tool in the real estate partnership to mitigate possible disputes and enhance the advantages offered by arbitration